Anti-Oxidant and Hepatoprotective Activities of Ziziphus mucronata Fruit Extract Against Dimethoate-Induced Toxicity - Kwape Tebogo Elvis; Chaturvedi Padmaja; Kamau Macharia; Majinda Runner (Journal of Pharmacopuncture, 2013)
Objective: The study was carried out to evaluate the hepatoprotective and antioxidant potential of Ziziphus mucronata (ZM) fruit extract. Methods: The different types of fruit extract were prepared by soaking the dry powdered fruit in different solvents followed by rotary evaporation. Each extract was tested for its phenol content and antioxidant activities. An in vivo study was performed in Sprague- Dawley (SD) rats. Thirty adult male SD rats (aged 21 weeks) were divided into six groups of five rats each and treated as follows: The normal control (NC) received distilled water while the dimethoate control (DC) received 6 mg/kg.bw.day-1 dimethoate dissolved in distilled water. The experimental groups E1, E2, E3, and E0 received dimethoate (6 mg/kg.bw) + ZMFM (100 mg/kg.bw-1), dimethoate (6 mg/kg.bw) + ZMFM (200 mg/kg.bw-1), dimethoate (6 mg/kg.bw) + ZMFM (300 mg/kg.bw-1), and ZMFM (300 mg/kg.bw-1) only. Both the normal control and the dimethoate control groups were used to compare the results. After 90 days, rats were sacrificed, blood was collected for biochemical assays, and livers were harvested for histological study. Results: High phenol content was estimated, and 2, 2- diphenyl-1-picryl hydrazyl radical (DPPH) spectrophotometric, thin layer chromatography (TLC) and 2, 2-Azobis-3-ethyl benzothiazoline-6-sulphonic acid (ABTS) assays showed a high antioxidant activity among the extracts. The preventive effects observed in the E1, E2 and E3 groups proved that the extract could prevent dimethoate toxicity by maintaining normal reduced glutathione (GSH), vitamin C and E, superoxide dismutase, catalase, cholineasterase and lipid profiles. The preventive effect was observed to be dose dependent. The EO group showed no extractinduced toxicity. Histological observations agreed with the results obtained in the biochemical studies. Conclusion: The study demonstrated that ZM methanol fruit extract is capable of attenuating dimethoate-induced toxicity because of its high antioxidant activity.